The nucleoprotein of influenza A virus inhibits the innate immune response by inducing mitophagy - Zhang, Bo; Xu, Shuai; Liu, Minxuan; Wei, Yanli; Wang, Qian; Shen, Wentao; Lei, Cao-Qi; Zhu, Qiyun (Autophagy, 2023)
Mitophagy is a form of autophagy that plays a key role in maintaining the homeostasis of functional mitochondria in the cell. Viruses have evolved various strategies to manipulate mitophagy to escape host immune responses and promote virus replication. In this study, the nucleoprotein (NP) of H1N1 virus (PR8 strain) was identified as a regulator of mitophagy. We revealed that NP-mediated mitophagy leads to the degradation of the mitochondria-anchored protein MAVS, thereby blocking MAVS-mediated antiviral signaling and promoting virus replication. The NP-mediated mitophagy is dependent on the interaction of NP with MAVS and the cargo receptor TOLLIP. Moreover, Y313 of NP is a key residue for the MAVS-NP interaction and NP-mediated mitophagy. The NP Y313F mutation significantly attenuates the virus-induced mitophagy and the virus replication in vitro and in vivo. Taken together, our findings uncover a novel mechanism by which the NP of influenza virus induces mitophagy to attenuate innate immunity. Abbreviations: ACTB: actin beta; ATG7: autophagy related 7; ATG12: autophagy related 12; CCCP: carbonyl cyanide 3-chlorophenyl hydrazone; co-IP: co-immunoprecipitation; COX4/COXIV: cytochrome c oxidase subunit 4; DAPI: 4ʹ,6-diamidino-2-phenylindole, dihydrochloride; EID 50 : 50% egg infective dose; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFP: green fluorescent protein; HEK: human embryonic kidney; hpi: hours post-infection; IAV: influenza A virus; IFN: interferon; IP: immunoprecipitation; LAMP1: lysosomal associated membrane protein 1; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MAVS: mitochondrial antiviral signaling protein; Mdivi-1: mitochondrial division inhibitor 1; MLD 50 : 50% mouse lethal dose; MOI: multiplicity of infection; NBR1: NBR1 autophagy cargo receptor; NP: nucleoprotein; PB1: basic polymerase 1; RFP: red fluorescent protein; RIGI: RNA sensor RIG-I; RIGI-N: RIGI-CARD; SeV: Sendai virus; SQSTM1/p62: sequestosome 1; TIMM23: translocase of inner mitochondrial membrane 23; TOLLIP: toll interacting protein; TOMM20: translocase of outer mitochondrial membrane 20; TUBA: tubulin alpha; Vec: empty vector; vRNP: viral ribonucleoprotein.